2018
DOI: 10.11114/jets.v6i10.3423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of 12 Weeks Football Training on the Posture of Young Male Basketball Players

Abstract: Posture is the most healthy and correct placement of each region in the body when compared to the whole body. The predominantly use of one side of the body disrupts the posture. A bad posture changes the center of gravity of the body and causes chronic skeletal and muscle soreness. It is aimed to determine whether there is a rehabilitative effect of football training that does not require the use of dominant arms on posture asymmetries which may occur in the basketball which requires the use of dominant arm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Studies on the use of specific sports to counteract postural disorders indicate that even in adult athletes, positive and lasting changes can be achieved through body posture re-education. For instance, a study by Kaplan [ 53 ] demonstrated positive effects on asymmetrical posture after 12 weeks of football training among basketball players. Małek et al [ 54 ] found that triathlon training contributes to maintaining normal postural muscle length, increased spine and chest mobility, and improved overall body posture.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the use of specific sports to counteract postural disorders indicate that even in adult athletes, positive and lasting changes can be achieved through body posture re-education. For instance, a study by Kaplan [ 53 ] demonstrated positive effects on asymmetrical posture after 12 weeks of football training among basketball players. Małek et al [ 54 ] found that triathlon training contributes to maintaining normal postural muscle length, increased spine and chest mobility, and improved overall body posture.…”
Section: Discussionmentioning
confidence: 99%
“…Posture is a crucial aspect of health, representing the proper alignment of body parts and a fundamental motor habit in daily activities. The mastery of postural control is essential for engaging in physical activities [16]. Adolescence, characterized by accelerated physical growth, changes in adipose tissue distribution, increased bone length, and higher joint forces, is a critical developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of basketball players conducted by Nam et al [ 67 ], the sample had curvature values in the range of 37–42°, which represents a difference of approximately 10° as compared with the normal range [ 68 ]. In addition, Kaplan [ 69 ], when comparing basketball players and a control group to determine posture, found that the basketball group had a lateral spinal curvature, head positioned in the right sagittal plane, pelvic tilt, and thoracic kyphosis [ 70 ].…”
Section: Discussionmentioning
confidence: 99%